Selective breeding of rats for high (HAB) and low (LAB) anxiety-related behaviour: A unique model for comorbid depression and social dysfunctions - Gryksa, Katharina (2023)
Animal models of selective breeding for extremes in emotionality are a strong experimental approach to model psychopathologies. They became indispensable in order to increase our understanding of neurobiological, genetic, epigenetic, hormonal, and environmental mechanisms contributing to anxiety disorders and their association with depressive symptoms or social deficits. In the present review, we extensively discuss Wistar rats selectively bred for high (HAB) and low (LAB) anxiety-related behaviour on the elevated plus-maze. After 30 years of breeding, we can confirm the prominent differences between HAB and LAB rats in trait anxiety, which are accompanied by consistent differences in depressive-like, social and cognitive behaviours. We can further confirm a single nucleotide polymorphism in the vasopressin promotor of HAB rats causative for neuropeptide overexpression, and show that low (or high) anxiety and fear levels are unlikely due to visual dysfunctions. Thus, HAB and LAB rats continue to exist as a reliable tool to study the multiple facets underlying the pathology of high trait anxiety and its comorbidity with depression-like behaviour and social dysfunctions.